Answer:
12.
Step-by-step explanation:
![b - 4a](https://tex.z-dn.net/?f=b%20-%204a)
Substitute this equation with a=3 and b=24:
![24 - 4(3)](https://tex.z-dn.net/?f=24%20-%204%283%29)
![24 - 12](https://tex.z-dn.net/?f=24%20-%2012)
![12](https://tex.z-dn.net/?f=12)
Answer:
Y = 32.7°
Step-by-step explanation:
We will apply the Cosine law in the given triangle XYZ,
x = 90 ft
y = 55 ft
z = 50 ft
We have to find the measure of angle Y.
y² = x² + z² - 2xzCosY
(55)² = (90)² + (50)² - 2(90)(50)cosY
3025 = 8100 + 2500 - 9000.cosY
9000.cosY = 10600 - 3025
cosY = ![\frac{7575}{9000}](https://tex.z-dn.net/?f=%5Cfrac%7B7575%7D%7B9000%7D)
= 0.84167
Y = ![\text{cos}^{-1}(0.84167)](https://tex.z-dn.net/?f=%5Ctext%7Bcos%7D%5E%7B-1%7D%280.84167%29)
Y = 32.68 ≈ 32.7°
Therefore, measure of angle Y = 32.7°
The dependent variable is 5 and the independent is 15
Answer:
(6, 9 ) and r = 3
Step-by-step explanation:
The equation of a circle in standard form is
(x - h)² + (y - k)² = r²
where (h, k) are the coordinates of the centre and r is the radius
Given
x² + y² - 12x - 18y + 108 = 0
Rearrange the x- terms and the y- terms together and subtract 108 from both sides, that is
x² - 12x + y² - 18y = - 108
To obtain standard form use the method of completing the square
add ( half the coefficient of the x and y terms )² to both sides
x² + 2(- 6)x + 36 + y² + 2(- 9)y + 81 = - 108 + 36 + 81
(x - 6)² + (y - 9)² = 9 ← in standard form
with centre = (6, 9 ) and r =
= 3